Healthy aging in sociocultural context - Scharlach, Andrew E.; Hoshino, Kazumi. (Routledge advances in sociology ;, 2013)
"Healthy Aging in Sociocultural Context examines two emerging trends facing countries throughout the world: population aging and population diversity. It makes a unique contribution to our understanding of these timely issues by examining their implications for healthy aging, a topic of increasing importance to policy-makers, planners, researchers, families, and individuals of all ages. The book focuses on three countries that provide important examples of these emerging global trends - Japan, Sweden, and the United States. Japan and Sweden are at the forefront in terms of healthy life expectancies, while the United States represents a country with considerable diversity. Examining these three countries together provides a unique opportunity to address questions such as the following: How can we understand differences in healthy life expectancy among different countries? What role might diversity play? And how might these effects change as geographic mobility increases diversity, even among societies that historically have been relatively homogeneous?"--